Paradise Regained The Regreening of Earth - Johnson, Les.; Matloff, Gregory L.; Bangs, C.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
What was our planet like before the advent of our modern civilization? What effect has our civilization had on the planet and its ecology? Paradise Regained begins by discussing these questions and then generates a scenario for the re-greening of Earth. It introduces new and innovative ideas on how humankind could use the resources of the Solar System for terrestrial benefit. The environmental challenges facing humanity today are too serious to be resolved simply by conservation and current technologies. Paradise Regained highlights the risk of humankind's future extinction from environmental degradation. Human population growth, climate change, and the diminishing sustainability of the few remaining habitats for wildlife are all analyzed. Rather than losing heart, we need to recognize that the answer to these problems lies in the development of space. Not only will extraterrestrial resources avert a crisis, but they will also provide the basis for continued technological and societal progress. The resources of the Solar System will help us meet our projected industrial needs. Space-based power generation systems will work synergistically with Earth-based conservation. The book concludes with a discussion on how closed ecological systems in space will function. This is a book that needs to be read urgently by many, if we are to save ourselves from environmental disasters and build a prosperous and sustainable future for all the creatures of Earth.
Space Utilization: A Moral Imperative -- I. Mythical Paradise -- Fire: Formation of Earth and the Solar System -- Earth Before Man: Utopia or Nightmare? -- II. Paradise Lost? -- The Environmental Dilemma: Progress or Collapse? -- Exploding Population -- Climate Change -- Vanishing Life -- Diminishing Energy -- Humans Before the Industrial Age: A Desirable Ecological Goal? -- III. Paradise Regained -- Raw Materials from Space -- Power from the Sun -- Environmental Monitoring from Space -- Protecting Earth -- Mitigating Global Warming -- Settling the Solar System -- Paradise Regained: An Optimistic Future.
Keywords: Engineering; Ecology; Astrophysics; Astronomy; Astronautics; Nature Conservation; Engineering; Aerospace Technology and Astronautics; Popular Science in Astronomy; Extraterrestrial Physics, Space Sciences; Ecology; Nature Conservation